2014
DOI: 10.5433/1679-0359.2014v35n2p973
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização morfoestrutural de fêmeas e machos jovens de ovinos naturalizados Sul-mato-grossenses “Pantaneiros”

Abstract: ResumoMedidas morfométricas são importantes para avaliar a variabilidade, determinar o padrão racial e a existência de dimorfismo sexual em um grupo genético. Com este objetivo foram realizadas 20 medidas morfométricas e uma medida ponderal em 338 animais do grupo genético de ovinos naturalizados Sulmato-grossenses pertencentes à Fundação Manoel de Barros, criadas no Centro Tecnológico de Ovinos (CTO) da Universidade Anhanguera-Uniderp localizado em Campo Grande-MS e a Universidade Federal da Grande Dourados. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…Grupa corta ligeramente caída. Cola con vellón denso y justo debajo del corvejón (Oliveira et al, 2014) (Figura 7).…”
Section: E F Bunclassified
See 1 more Smart Citation
“…Grupa corta ligeramente caída. Cola con vellón denso y justo debajo del corvejón (Oliveira et al, 2014) (Figura 7).…”
Section: E F Bunclassified
“…La caracterización morfométrica de los grupos genéticos, realizada mediante medidas corporales, y los índices zootécnicos son de gran importancia para comprender el potencial productivo de los biotipos y sus habilidades para la exploración comercial (Carmona, 2011). Oliveira et al (2014) 172…”
unclassified
“…There is no doubt that several research outcomes have contributed to describing the performance of carcass and milk from Pantaneiro sheep [13,15,16]. This might put conservation strategies closer to market opportunities and prospects for regional development.…”
Section: Introduction 1general Backgroundmentioning
confidence: 99%
“…An analysis of morphometric characterization, using 338 naturalized sheep from Mato Grosso do Sul and performed 20 morphometric measurements, concluded that the females of this genetic group have relatively large heads (32.4 cm), and this feature along with the length of the skull (24.2 cm) are larger in females than in males [23].…”
Section: Features Of Pantaneiro Sheepmentioning
confidence: 99%